Predictive Value of Conventional Computed Tomography: in Determining Proximal Extent of Abdominal Aortic Aneurysms and Possibility of Infrarenal Clamping - Posacioglu, Hakan (2002)
The present study aimed to evaluate the diagnostic reliability of computed tomography in determining the proximal extent of abdominal aortic aneurysms and the possibility of infrarenal clamping. Preoperative computed tomographic findings, together with the operative data for 95 patients, were retrospectively analyzed in light of the operative findings. Eighty-nine (93.68%) of the patients were men and 6 (6.32%) were women, with a mean age of 66.27 ± 18.14 years. Diagnosis of infrarenal aneurysm by computed tomography was confirmed at the time of surgery in 91 (95.79%) of 95 patients. The negative-predictive value of computed tomography in detecting supra-aneurysmal renal arteries was found to be 95.79%. The specificity was 98.91%. Infrarenal cross-clamping was performed in 59 (62.11%) of 95 patients, whose aortic segments between the renal artery orifices and the proximal borders of the aneurysms had a mean length of 26.4 ± 7.11 mm by computed tomography. Suprarenal clamping was required in 36 (37.89%) of the 95 patients, whose aortic segments had a mean length of 12.7 ± 3.48 mm. We conclude that conventional computed tomography is reasonably accurate in determining the proximal extent of abdominal aortic aneurysms. Although there is a high rate of error in determining the possibility of infrarenal clamping when no specific measurements are taken, infrarenal clamping can be planned when measurement by computed tomography shows a length of ≥26 mm between the renal arteries and the proximal extent of the aneurysm. In patients with shorter aortic segments, suprarenal aortic clamping should be considered. (Tex Heart Inst J 2002;29:172–5)